Transformative Dynamics of the Economy of Kosovo: A Perspective on History and Development of Foreign Direct Investment - Zogjani, Jeton; Kovaci-Uruci, Fife; Zogjani, Agon (Naše gospodarstvo/Our economy, 2024)
This paper presents an in-depth overview of foreign direct investments (FDI) in Kosovo’s economy over more than twenty years. FDI has played a central role, proving indispensable to the development of Kosovo’s economy. Thus, FDI is primarily directed towards economic activities like real estate, finance, manufacturing, construction, etc. In terms of the legal framework, Kosovo has approved a range of regulations and laws with the primary goal of protecting, attracting and encouraging foreign investors to invest. However, obstacles such as political instability, energy insecurity, delayed EU integration, and regional political tensions are recognized as the main barriers affecting FDI in Kosovo. Finally, Kosovo should develop suitable policies to boost its investment competitiveness, attract multinational enterprises for investment opportunities, and prioritize less attractive economic sectors for investment of FDI.